Fostering Empathy Through Play: The Impact of Far From Home on University Staff’s Understanding of International Students - Shuanghui Sofia Shan; Sam Illingworth (Behavioral Sciences, 2025)
This study investigates the potential of Far From Home, a non-digital board game, as an innovative tool for fostering empathy among university staff towards international students. International students face multifaceted challenges—linguistic barriers, cultural dissonance, and systemic inequities—yet traditional staff training often fails to cultivate the perspective-taking required for meaningful support. Using a mixed-methods approach, we analysed data from 82 participants across 10 game sessions, including surveys (n = 27), recorded gameplay observations, and semi-structured interviews (n = 6). Thematic analysis explored how role-playing as student avatars and collaborative problem-solving influenced staff empathy. The results demonstrated the game’s effectiveness in bridging cultural gaps, with participants reporting a heightened awareness of structural barriers and reduced stereotyping. Notably, the emergent findings suggested a “contrast commitment” effect, where witnessing biassed behaviours reinforced staff’s dedication to equitable practices. This study advocates for game-based training as a complement to existing programmes, with future research needed to assess longitudinal impacts. Potential applications include adapting the framework for other marginalised student groups and institutional contexts.